Applying Acupuncture as Part of Multidisciplinary Treatment for Locked-in Syndrome: A Case Report - Liu Tsung-Han; Tsung-Han Yang (Journal of Acupuncture Research)
Multidisciplinary approaches are commonly employed in the rehabilitation of patients with locked-in syndrome (LIS); however, reports on acupuncture treatment of LIS are limited. A 56-year-old male was diagnosed with a pontine infarction, presenting with a National Institutes of Health Stroke Scale score of 23. By week 3 post-stroke, the patient showed LIS signs, as he could communicate through eye blinking while remaining quadriplegic. By week 4, the patient began receiving traditional acupuncture therapy for a total of 9 weeks. Acupuncture points used included LR3, SP3, SP4, K2, SP6, SP8, SP9, LI4, LI11, L10, GV20, EXTRA-1, and EXTRA-8. In the meantime, the patient received repetitive transcranial magnetic stimulations, regular physiotherapy, occupational therapy, and speech therapy. By week 11, the patient could voluntarily move his right fingers and toes and was successfully weaned off the tracheostomy. By week 12, he was discharged from the hospital.